Internalizing Pancasila Values on Generation Z Cadets of Medan Aviation Polytechnic in Social Media - Samosir, Hairul Amren; Akbar, Muhammad Caesar (Universitas PGRI Kanjuruhan Malang, 2023)
Nowadays, social media is always used as a means of spreading fake news, hate speech, and bullying. To overcome this, social media users must internalize the values of Pancasila in using social media. This study aims to analyze the influence of internalizing Pancasila values on Generation Z cadets of the Medan Aviation Polytechnic in social media. Internalization of Pancasila values is carried out through learning Pancasila values. Qualitative methods and 96 cadets as samples were used in this study. The research data was obtained by observing the posts of cadets on social media twice, namely after the pre-test and post-test. Pre-test and post-test are carried out before and after the internalization of Pancasila values, respectively. Based on the results of the study, it is known that cadets who behave positively increased after the internalization of Pancasila values, namely from 35 people to 83people. Meanwhile, cadets who behaved neutrally decreased from 48 to 10, and the number of cadets who behave negatively dropped from 13 people to 3 people.